The Jossey-Bass guide to strategic communications for nonprofits : - Bonk, Kathy (Jossey-Bass, 1999)
This nuts-and-bolts workbook is a tool kit for organizations that want to create successful communications strategies. No matter their size or planning experience, nonprofits can use this guide to enhance their profiles in the media, increase name recognition, boost fundraising, recruit membership, and advance changes in public policy. With a clear mission and the right communications skills, even small volunteer organizations can succeed in designing, planning, and implementing strategic public interest campaigns.